Development of Python applications for learning computational physics (2017)
This paper describes an application developed for learning simulation algorithms based on classical mechanics concepts. Electronics Engineering and Computer Science students at the Universidad de los Llanos study computational physics, using Particle kinematics (PK), as one activity of Dynamic Systems research group. Python, the programming language selected, facilitated the portability and access to the libraries necessary for representing particles. The main Python Libraries used in this process are matplotlib, numpy, PyQt4, scipy, Tkinter and VPython. These libraries allow the simulation of uniform motion, linear accelerated movement, objects in free fall and projectile motion. Additionally they are useful for generating GUIs to show data in tables and graphics. The GUIs were implemented using the Tkinter and PyQt4 libraries, where the latter facilitated the development with the help of Qt Designer software Tools.